PENGARUH BELANJA PEGAWAI, BELANJA BARANG JASA, BELANJA MODAL DAN JUMLAH ASET TETAP DAERAH TERHADAP KEMAMPUAN KEUANGAN PEMERINTAH KABUPATEN KOTA DI PROVINSI SUMATERA SELATAN TAHUN 2008 - 2013 - Septa Efrieni Putri (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2014)
Regional Autonomy aims to realize the independence of regional development in all aspects of life. Through autonomy, all regions in Indonesia are expected to be able to carry out all government affairs and development by relying on local own revenue (PAD). The main characteristic that embodies an autonomous region capable of berotonom lies in the financial capacity of the region. This means that the autonomous regions must have the authority and ability to explore their own financial resources to manage and use sufficient finances to finance the implementation of local government. This study aims to determine the effect of personnel expenditure, goods and services expenditure, capital expenditures and total fixed assets of the district to the financial capacity of municipal districts in the province of South Sumatra, amounting to 15 districts of the city period 2008-2013. The data used in this research is panel data that is quantitative. Further data in the analysis with Random Effects method with the help of data processing software eviews version 6. The results of this study conclude that personnel expenditure, goods and services expenditure, capital expenditures and total fixed assets area together significantly influence the financial capacity of the region. Employee expenditure variable and service spending variable partially have a significant influence with positive coefficient direction, while variable of fixed asset area partially have significant effect with negative coefficient direction, while capital expenditure variable have no significant effect to to local financial ability.